DESAIN BENDUNG KALIGENDING PADA DAERAH NON CEKUNGAN AIR TANAH (NON – CAT) - Arya Pratapa Priyahita; Trian Maulana; Robert J. Kodoatie; Hary Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
In 1992, Kaligending Weir was Built at Kaligending Village, Karangsambung District in Kebumen. In 1998 the Kaligending Weir was dismantled due to the flood at Karangsambung which the people considered was caused by the weir. this made the water unable to enter the intake and made the Irigated area not being supplied by the water from Kaligending Weir. The Kaligending Weir is located on non groundwater area. At non-Groundwater basin, water flows only on the soil water zone, meanwhile at groundwater basin, there are water flow in the ground water zone layer. Calculating the water availability is needed to fulfill the irigated water demand. Water availability is calculated using modified F.J. Mock Method. Kaligending Weir was constructed at Luk Ulo River with a 253,52 km2 basin area and 2984 Ha irrigated area. Kaligending Weir is planned by using 1361,19 m3/s flood discharge with a 50 years period calculated by FSR JAWA SUMATERA method. Kaligending Weir uses a 3,7 tall round crest. The stilling basin is 39 m long and 7,72 m wide. By considering the volume and unit price, Kaligending Weir cost Rp. 133,796,306,000.